Living donor liver transplantation for pediatric patients with metabolic disorders: The Japanese multicenter registry. (28th November 2013) - Kasahara, Mureo; Sakamoto, Seisuke; Horikawa, Reiko; Koji, Umeshita; Mizuta, Koichi; Shinkai, Masato; Takahito, Yagi; Taguchi, Tomoaki; Inomata, Yukihiro; Uemoto, Shinji; Tatsuo, Kuroda; Kato, Shunichi
Abstract LDLT is indicated for a variety of metabolic disorders, primarily in Asian countries due to the absolute scarcity of deceased donor LT. We analyzed data for all pediatric LDLTs performed between November 1989 and December 2010, during which 2224 pediatric patients underwent LDLT in Japan. Of these patients, 194 (8.7%) underwent LDLT for metabolic disorders. Wilson's disease (n = 59; 30.4%) was the most common indication in the patients with metabolic disorders, followed by OTCD (n = 40; 20.6%), MMA (n = 20; 10.3%), and GSD (n = 15; 7.7%). The one‐, five‐, 10‐, and 15‐yr patient and graft survival rates were 91.2%, 87.9%, 87.0%, and 79.3%, and 91.2%, 87.9%, 86.1%, and 74.4%, respectively. Wilson's disease and urea cycle deficiency were associated with better patient survival. The use of heterozygous donors demonstrated no negative impact on either the donors or recipients. With regard to X‐linked OTCD, symptomatic heterozygote maternal donors should not be considered potential donor candidates. Improving the understanding of the long‐term suitability of this treatment modality will require the registration and ongoing evaluation of all patients with inherited metabolic disease considered for LT.